Thomas S. Kuhn y la función de los instrumentos científicos en el desarrollo de las ciencias físicas - Mayoral de Lucas, Juan Vicente (ENDOXA, 2005)
This is a study of Kuhn’s ideas regarding the role of physical instruments in the histórica! development of physical sciences. Its approach to Kuhn’s thought is primarily historical and biographical, and it makes extensive use of Kuhn’s archival sources at MIT to settle a group of ideas of Kuhn’s as a basis out of which that role follows almost naturaily. It starts out with an introduction to the «operational» history of science Kuhn found as an assistant to Conant. It runs on talking about Kuhn’s divergent opinions about the proper place of concepts in both physical research and theory. It ends with an account of Kuhn’s new historical visión of science (including the role of instruments in it), and its relations to that of Alexandre Koyré’s (another key influence on his thought).